Rice Husk Based Charcoal Biobriquette Production Technology With Carbonization Process In Rural Environment In Pasie Laweh Nagari, Lubuk Alung District - Riski Gunawan Nasution; David Rian Mahendra (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
This community service program aimed to develop rice husk-based charcoal biobriquette production technology through a carbonization process in Pasie Laweh Nagari, Lubuk Alung District. The initiative sought to address the underutilization of rice husk waste, which is abundant in the region due to its significant rice farming activities. By converting agricultural waste into eco-friendly biobriquettes, the program provided an alternative energy source while enhancing the economic value of waste for local farmers. The implementation involved training, technology transfer, and hands-on mentoring, resulting in the production of biobriquettes with a diameter of 2 cm, height of 5 cm, and a burning duration of 2--3 hours per unit. The program achieved a 95% participation rate, with active involvement from farmers, youth groups, and local MSMEs. Quantitative analysis through pre-test and post-test revealed a significant increase in participants' knowledge and skills. The average scores for understanding the concept of biobriquettes increased from 45% to 85%, carbonization techniques from 35% to 80%, understanding of economic benefits from 50% to 90%, and practical skills from 30% to 75%. Economic benefits included a 40% reduction in fuel costs for businesses and 30% savings for households. The success of the program highlights the potential of biobriquettes as a sustainable energy solution and underscores the importance of community empowerment, institutional support, and technological innovation in rural development.